The Use of False Flag Operations as a Subterfuge to Perpetrate Terrorism in the Name of Islam - Guru Dev Teeluckdharry (Recent Trends in Arts and Social Studies Vol. 6, 2023)
This paper has been prepared to shed light on false flag operations. It attempts to portray the relationship between radical terrorists of Islam and orchestrators of false flag operations of Zionism. Why is Islam being demonized? Who are those who are taking advantage of this and why the reputation of Muslims are being tarnished by Zionists? Who are those behind the apocalyptic events of 9/11? How can we condemn Osama Ben Laden for being the orchestrator of 9/11 although he has not been condemned by an International Court of Law and Justice? Why conspiracy theories are being used to shift the blame solely on Al-Qaeda and ISIS? Why so-called conspiracy facts are not being considered by governments worldwide? Why false flag operations by Mossad and Shin Bet are not being reported by the media nowadays in order to trigger an inquiry by the US government? This paper is an attempt to provide thought-provoking answers to these pertinent questions.